La santé des francophones de l'Ontario. Un portrait régional tiré des Enquêtes sur la santé dans les collectivités canadiennes (ESCC) - Bouchard, Louise; Batal, Malek; Imbeault, Pascal; Gagnon-Arpin, Isabelle; Makandi, Ewa; Sedigh, Golnaz (Réseau de recherche appliquée sur la santé des francophones de l'Ontario, 2012)

The health of Francophones in Ontario. A region-by-region portrait developed from the Canadian community health survey (CCHS) - Bouchard, Louise; Batal, Malek; Imbeault, Pascal; Gagnon-Arpin, Isabelle; Makvandi, Ewa; Sedigh, Golnaz (Réseau de recherche appliquée sur la santé des francophones de l'Ontario, 2012)

Rapport d'enquête d'évaluation des besoins et de services de santé des francophones du Sud-Est - Bouchard, Louise; Gagnon-Arpin, Isabelle; Makvandi, E.wa (Réseau de recherche appliquée sur la santé des francophones de l’Ontario, 2012)

Workforce utilization of visible and linguistic minorities in Canadian nursing - Premji, Stephanie; Etowa, Josephine. B. (Journal of Nursing Management, 2012)
Background There is ample evidence of ethnic and linguistic segregation in the Canadian labour market. However, it is unknown if there is equitable representation of visible and linguistic minorities in nursing professions. Methods We cross-tabulated aggregate data from Statistics Canada’s 2006 Census. Analyses examined the distribution of visible and linguistic minorities, including visible minority sub-groups, among health managers, head nurses, registered nurses, licensed nurses and nurse aides for Canada and major cities as well as by gender. Results In Canada and its major cities, a pyramidal structure was found whereby visible and linguistic minorities, women in particular, were under-represented in managerial positions and over-represented in lower ranking positions. Blacks and Filipinos were generally well represented across nursing professions; however, other visible minority sub-groups lacked representation. Conclusions Diversity initiatives at all levels can play a role in promoting better access to and quality of care for minority populations through the increased cultural and linguistic competence of care providers and organizations.

Regards croisés Ontario-Québec : les services de soins de santé mentale des communautés de langue officielle en situation minoritaire de 1950 à nos jours - Thifault, Marie-Claude; Lebel, Marie; Perreault, Isabelle; Desmeules, Martin (Reflets, 2012)
Considérant qu’un Canadien sur neuf hospitalisé pour maladie mentale retournera à l’urgence moins d’un mois après sa sortie d’hôpital, il importe de documenter, dans une perspective socio-historique, les itinéraires « transinstitutionnels » des personnes souffrant de troubles psychiques. Nous proposons ici une note de recherche sur l’enquête que nous menons sur l’évolution des services de soins de santé mentale des communautés de langue officielle en situation minoritaire, en particulier, les communautés francophones de l’Est et du Nord ontarien ainsi que de la communauté anglophone de l’Ouest du Québec. Ces regards croisés entre deux régions francophones de l’Ontario et le Montréal anglophone visent une meilleure compréhension de l’impact des facteurs de « langue de service » et de « culture » sur la santé mentale des communautés francophones en situation minoritaire (CFSM). Mots-clés : services de santé mentale, désinstitutionnalisation, minorités linguistiques, Ontario, Québec

Construction of Francophone families’ health literacy in a linguistic minority situation - Zanchetta, Margareth. Santos; Kaszap, Margot; Mohamed, Mohamed; Racine, Louise; Maheu, Christine; Masny, Diana; Cèsar, Ines; Maltais, Claire; Sangwa-Lugoma, G.; Lussier, Nancy; Kinslikh, Diana (Alterstice, 2012)
With the  increase  in  international  mobility,  healthcare  systems  should  no  longer  be  ignoring  language  barriers.  In  addition  to  the  benefit  of  reducing  long‐term  costs,  immigrant‐friendly  organizations  should  be  concerned  with  mitigating  the  way  language  barriers  increase  individuals’  social  vulnerabilities  and  inequities  in  health  care  and  health  status.  This  paper  reports  the  findings  of  a  qualitative,  exploratory  study  of  the  health  literacy  of  28  Francophone  families  living  in  a  linguistic‐minority  situation  in  Canada.  Analysis  of  interviews  revealed  that  participants’  social  vulnerability,  mainly  due  to  their  limited  social  and  informational  networks,  influenced  the  construction  of  family  health  literacy.  Disparities  in  access  to  healthcare  services  could  be  decreased  by  having  health  professionals’  work  in  alliance  with  Francophone  community  groups  and  by  hiring  bilingual  health  professionals.  Linguistic  isolation  and  lack  of  knowledge  about  local  cultural  organizations  among  Francophone immigrants  were  two  important  findings  of  this  study.